Farmers’ Awareness and Perception about Climate Change in the Indo-Gangetic Plain Region of India (Indian Journal of Extension Education, 2024)
Climate change is negatively impacting agriculture productivity worldwide. Accordingly, it becomes necessary to know the level of farmers’ awareness about climate change. The study was conducted in the year 2023 to examine farmers’ awareness and perceptions about nature, and the impact of changes in climate patterns on agriculture in India’s Indo Gangetic Plain (IGP) region. The study is based on a survey of 400 farmers, selected conveniently from five districts of Uttar Pradesh, a prominent province of the IGP region. The weighted average mean and chi-square test were applied to analyze the primary data. The findings indicate that farmers of the sampled area were aware of the problem, they get weather-related information from multiple sources like television, newspapers, etc. Almost half of the respondents in the sampled area strongly consider climate change as anthropogenic as well as naturogenic. Farmers perceived that reduced crop yields as the premier ultimatum of climate change in agriculture. The results unveil that the contrasting income groups have different levels of awareness of climate change similarly youth and educated farmers rely on their specific sources of weather-related information.